2017
DOI: 10.1210/en.2017-00103
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Ablation of the LIF Receptor in the Murine Uterine Epithelium Results in Implantation Failure

Abstract: The cytokine leukemia inhibitory factor (LIF) is essential for rendering the uterus receptive for blastocyst implantation. In mice, LIF receptor expression (LIFR) is largely restricted to the uterine luminal epithelium (LE). LIF, secreted from the endometrial glands (GEs), binds to the LIFR, activating the Janus kinase–signal transducer and activation of transcription (STAT) 3 (Jak-Stat3) signaling pathway in the LE. JAK-STAT activation converts the LE to a receptive state so that juxtaposed blastocysts begin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 55 publications
0
23
0
1
Order By: Relevance
“…Using gene expression microarray analysis, we discovered the downregulation of CDYL mRNA in the endometrial samples obtained from patients with RIF (Figure 1) (Guo et al, 2018). We further detected the significantly lower expression of CDYL protein in the RIF group, consistent with the expression of LIF ( Figure 1C), which is a marker of endometrial receptivity (Paiva et al, 2009;Cheng et al, 2017;Vagnini et al, 2019). In addition, the results obtained from ROC analysis revealed the high sensitivity and specificity to discriminate endometrial receptivity based on the CDYL expression levels of the endometrial tissues.…”
Section: Discussionmentioning
confidence: 61%
“…Using gene expression microarray analysis, we discovered the downregulation of CDYL mRNA in the endometrial samples obtained from patients with RIF (Figure 1) (Guo et al, 2018). We further detected the significantly lower expression of CDYL protein in the RIF group, consistent with the expression of LIF ( Figure 1C), which is a marker of endometrial receptivity (Paiva et al, 2009;Cheng et al, 2017;Vagnini et al, 2019). In addition, the results obtained from ROC analysis revealed the high sensitivity and specificity to discriminate endometrial receptivity based on the CDYL expression levels of the endometrial tissues.…”
Section: Discussionmentioning
confidence: 61%
“…One study suggested that uterine receptivity and implantation was regulated by the Lif-Lifr/gp130-JAK/STAT3 signaling pathway. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, the function of selected cytokines and chemokines in the immunologic interaction between the mother and the trophoblast is being discovered in several cases. For instance, the importance of LIF in early stages of embryo implantation has become clear [120]; moreover, emerging evidence strongly suggests that on the one hand, the major pro-inflammatory cytokines IL-1β and TNF-α, released by uterine macrophages sensitized by seminal fluid antigens, contribute to the development of tolerogenic DCs (tDCs) [54]; on the other hand, after embryo implantation, the anti-inflammatory cytokines IL-10 and TGFβ play key roles in the regulation of tolerogenic DCs in the decidua, in reducing the local inflammatory response and in driving the expansion of Treg cells [33,54]. Among the chemokines, CXCL1 was found to be markedly upregulated in decidualized human endometrial stromal cells [121].…”
Section: Cytokine/chemokine Network and The Maternal-fetal Immune Cromentioning
confidence: 99%